Mercy Watson to the rescue - DiCamillo, Kate; Van Dusen, Chris (Cambridge, MA : Candlewick Press, 2005)
After Mercy the pig snuggles to sleep with the Watsons, all three awaken with the bed teetering on the edge of a big hole in the floor.
Ages 6-8.
450
Accelerated Reader/Renaissance Learning
Accelerated Reader AR
Keywords: Swine -- Juvenile fiction; Neighbors -- Juvenile fiction; Fire departments -- Juvenile fiction; Humorous stories